Using a Socio-technical Approach to Build a National Extranet Portal in the Medicines Regulatory Sector - Drobec, Marko (Array, 2014)
The aim of this paper is to show the process of planning, building and establishing of the extranet portal of Croatian Agency for medicinal products and medical devices relying heavily on the future users’ involvement, suggestions and input in all stages of the process. Agency for medicinal products and medical devices is Croatian national competent authority (NCA) with the mandate of regulation of pharmaceutical products. The authors explain that the regulation process includes submission of medicinal products’ dossiers from industry to the Agency, interaction during assessment of documentation and gaining approvals for the products. At the moment, in Croatia, these processes are using conventional resources, i.e. paper dossiers and conventional communication channels like registration office and conventional correspondence. Meanwhile, regulatory processes worldwide and in the EU have been enhanced by using different web portals and by shifting to electronic medicinal products documentation in standard format called "electronic common technical document (eCTD)". In this paper the authors analyse the process of launching an internal project by the Croatian NCA aiming to build a web portal for submission of data and dossiers, communication and interactive work with the industry. The portal will be created for pharmaceutical companies that are external users of Agency’s services. This project has gathered and involved industry representatives as the future users of the extranet portal. The authors point out that the benefits from this method of interactive extranet portal building, involving all stakeholders, are twofold. Benefits on the industry side and on the Agency side. The portal, the authors emphasise, will have elements that are in line with the three socio- technical layers of web. The portal will allow read-only access to the data about medicines that are gathered and maintained by the Agency and this is a measure that supports the Web 1 layer. The Web 2 concept is supported as the portal enables direct communication of industry representatives with the Agency’s employees through messages and document exchange, as well as direct communication between industry representatives. The Web 3 functions are also supported by the portal's initiation of medicinal products’ regulatory activities through online forms and electronic documentation exchange as well as automatic notifications of users on certain procedure changes.